Electrostatics determine vibrational frequency shifts in hydrogen bonded complexes - Dey, Arghya; Mondal, Sohidul Islam; Sen, Saumik; Ghosh, Debashree; Patwari, G. Naresh (Physical Chemistry Chemical Physics, 2014)
The red-shifts in the acetylenic C-H stretching vibration of C-H center dot center dot center dot X (X = O, N) hydrogen-bonded complexes increase with an increase in the basicity of the Lewis base. Analysis of various components of stabilization energy suggests that the observed red-shifts are correlated with the electrostatic component of the stabilization energy, while the dispersion modulates the stabilization energy.